(untitled) (Universal International Scientific Journal, 2026)
This article explores the axiological aspects of A.P. Chekhov’s prose through the lens of gender self-determination in the intellectual sphere. The concepts of "labor," "knowledge," and "freedom" are analyzed as fundamental elements of the worldview of Chekhov’s heroines. The author argues that the writer’s ethical and philosophical principles shaped the prototype of the modern female researcher, focused on social progress and scientific inquiry. Drawing on contemporary literary approaches, the study examines Chekhov’s work as a link between classical humanism and contemporary achievements of women in science.